(untitled) (E Global Congress, 2023)
Although phraseology has not been formed as a separate part of linguistics for a long time, the history of its origin goes back to the first stages of language development. This field, of course, requires linguists to thoroughly study its general and specific laws. This paper widely presents phraseological units expressing positive emotions.